BAHASA WANITA DAN PRIA PADA KOLOM TANGGAPAN THREAD “PEMERASAN DAN PELECEHAN SEKSUAL OKNUM DOKTER” - Nesthy Kheren; Sarmiati Mia; Ernita Arif; Sazili Saman (Jurusan Ilmu Komunikasi Universitas Andalas, 2021)
Various social phenomena are often expressed on the social media twitter to attract responses from the public around the user. One of the interesting public responses in communication studies is language style. The issue of sexual harassment and violence against women is a common topic which gets a lot of response from the public. This research aims to analyze the differences between women and man language on the response column from a thread of twitter social media that is about a woman who had encountered a pressure and sexual harassment by the doctor who carried out the rapid test of SARS-CoV-2 on Soekarno-Hatta International Airport. This research was using qualitative content analysis approach toward thread’s response column on the twitter. We have found that the language style of man and women on the thread were different. The language of women relatively unclear compare to the man. The sentences created by the women used a lot of question tag at the end, whereas a man relatively did not. Women also did reluctantly to cuss and abuse compare to man. Women were relatively involved in conversation related with heart while men relatively involved in report conversation. Responses or interruptions by women were not to control, challenge, or threaten, but to support or emphasize the conversation. Meanwhile, men used more instrumental talk, report information, solve problems, and solve problems through information exchange. We also found a similarity between women and man, which was a language of draw conclusion.